Life in silico and the program of the ethics of rightmindedness - Czerny, Janusz (Folia Philosophica, 2005)
The author of the article employs the recentivistic idea of „here-now-being” for the explanation of the phenomena of life. According to John Allman life appeared in strictly, not to say rigorously, defined physical, chemical and time conditions. Janusz Czerny tries to prove that the idea of presenting reality in „here-now-being” corresponds with the main theses of modern science. The theory of chords and the phenomenon of life are equivalent to the context of „here-now-being”, which was introduced by Józef Bańka in his philosophy. In his article Janusz Czerny makes an attempt to introduce the philosophical ideas of recentivism to the language of modern science.